Development of a load monitoring system for residential purposes - Kang, Vincent Jia Han (2018)
In the 21st Century, where technology is heavily dependent on the electricity to function and served its purposes, we tend to consume a massive amount of electricity knowing that natural gases are replenishing faster than it is being replenished. As a result, this the project aims to develop a load monitoring system for residential units to better monitor their load consumption and aims to reduce the end-user electrical consumptions. Non-Intrusive Load Monitoring (NILM) is a technic whereby using only one sensor measuring devices to capture the total load consumption and identify each load appliances among the total energy power. In this way, it will provide the user on how much each load contributes to their power consumption daily, and thus encourage them to monitor their load properly. NILM system mainly has 2 components in this project, mainly the hardware design and the software approach. Electrical Data is being captured by the Yokogawa Power Meter, the information is then transmitted to the host machines via RS-232 Bluetooth Connection. In the host machine, both LabVIEW and MATLAB are used for designing the algorithm. Steady-state analysis is used in identifying the load type. Upon exceeding the power limitation set by the user, both a warning light will be issued on the Graphic User Interface (GUI) and an E-Mail notification to alert the user the power exceeds and the appliances contributing to the exceeding of power limit. Lastly, a GUI is developed to display all information required to the user based on a real-time scenario. The result of this project is to encourage the usage of this monitoring system to monitor their daily energy consumption, and thus cut-off unnecessary electrical appliances.